(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
The Vitreous Humor (VH) is a transparent, gel-like substance that fills the space between the lens and the retina in the eye. It helps maintain the eye’s shape, provides support to the retina, and allows light to pass through to the retina where images are formed. The major function of this fluid is to support the shape of the eye and transmit light to the retina. In this article, the effect of VH and its biochemical constituents since the time of death has been analyzed. This research also demonstrates the changes within biochemical constituents of VH as time increases after the death of a person. Besides that, this research is significantly beneficial for future researchers to evaluate changes in levels of VH after death and correlation with blood levels. Objective: To determine Post Mortem Interval from Potassium (K+) concentration in Vitreous, correlation of biochemical constituents with both eyes, and an additional objective is the correlation of levels of Biochemical Constituents i.e. Na+, K+, Cl-, and Urea in Vitreous and Blood. Material and Method: This study was conducted on the human dead bodies brought for medico-legal autopsy to the mortuary wing of Department of Forensic Medicine & Toxicology, Dr. RPGMC, Kangra at Tanda over a length of one year after obtaining informed consent. “Vitreous Humor” samples were collected from both eyes, first from the right eye and then from the left eye after external examination of the dead body at the time of post-mortem examination. Collecting blood directly from the heart and analyzing ocular fluids can be crucial for accurate assessments. For instance, VH is often analyzed in forensic investigations